A comparative Life Cycle Assessment of two sister cruise ferries with Diesel and Liquefied Natural Gas machinery systems. (July 2021) - Cucinotta, Filippo; Raffaele, Marcello; Salmeri, Fabio; Sfravara, Felice
Highlights: A comparative LCA between a Diesel and LNG fuelled sister ships have been performed. The number of LNG ships is growing, but there is a lack on their impact evaluation. The comparison assessment has been carried out in four different areas of protection. The study has investigated the climate change due to the methane leakage and slip. Climate change, human health, ecosystem and resource depletion results are discussed. Abstract: To contrast the naval emissions in terms of Sulphur and Nitroxides, recently, the institution of Emission Control Areas has increasingly prompted shipowners to choose new-generation engines capable of using Liquified Natural Gas as a marine fuel. This study presents a comparative Life Cycle Assessment, cradle-to-grave, between two different engines on a cruise ferry. One is a traditional Diesel machinery system and the other is a Liquified Natural Gas one. The two configurations have been analysed within 17 different impact categories in terms of climate change, human health, resourced depletion and ecosystems. The studied phases of the ship's life were the building, operation and dismantling. The results showed and quantified the environmental differences deriving from the use of Liquified Natural Gas in all the phases of the life of the ship. Generally, the LNG propulsion has shown to be more environmentally performing, but, particularly interesting are the results in terms of climate change, influenced by lower CO2 emissions but also by the phenomenon of methane slip that can increase the CO2 -equivalent effect. The energy costs of transport and liquefaction of gas also have an impact to consider. Analyses of uncertainty on the data and of sensitivity on fuel consumptions and losing of steel during the shipbuilding were carried out.